DAMPAK PRIVATISASI PADA KINERJA KEUANGAN BADAN USAHA MILIK NEGARA (BUMN) DI INDONESIA - Aprilina, Vita (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2013)
This study aims to examine the differences in financial performance before and after the privatization of state enterprises. The population in this study is all state-owned companies in Indonesia, while the sample in this study for phase I testing of the years 1993-2010, phase II testing of the years 2007- 2011, namely, doing an IPO and listing on the Indonesia Stock Exchange selected by purposive sampling method. This study used t-test. The results showed there is no difference performance in the company's financial before and after the privatization of state enterprises.